Why was the August 2010 Zhouqu landslide so powerful? - Ren, Diandong; Leslie, L.; Lynch, Mervyn; Duan, Q.; Dai, Y.; Shangguan, W. (Moskovskii Gosudarstvennyi Universitet im. M.V. Lomonosova * Fakul'tet Geografii, 2013)
On August 8, 2010 in the north western Chinese province of Gansu, rainstorm-triggered debris flow devastated the small county of Zhouqu. A modelling study, using a new multiple-phase scalable and extensible geo-fluid model, suggests that the cause is the result of an intersection of several events. These were a heavy rainstorm, not necessarily the result of global warming, which triggered the landslide and followed a drought that created surface cracks and crevasses; the geology of the region, notably the loess covering heavily weathered surface rock; and the bedrock damage, which deepened the surface crevasses, inflicted by the 7,9magnitude Wenchuan earthquake of May 12,2008. Deforestation and topsoil erosion also contribute. The modelling results underscore the urgency for a high priority program of revegetation of Zhouqu county, without which the region will remain exposed to future disastrous,‘ progressive bulking’ type landslides.